2018
DOI: 10.1088/1361-6595/aac0e9
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent modeling of self-organized patterns of spots on anodes of DC glow discharges

Abstract: Self-organized patterns of spots on a flat metallic anode in a cylindrical glow discharge tube are simulated self-consistently. A standard model of glow discharges is used, comprising conservation and transport equations for a single species of ion and electrons, written with the use of the drift-diffusion and local-field approximations, and the Poisson equation. Only processes in the near-anode region are considered and the computation domain is the region between the anode and the discharge column. Multiple … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…43 Bieniek et al also applied the same approach to simulate SOPs formed on the anode of DC glow discharge and found that the anode SOPs are related to the change in the sign of the near anode voltage. 44 Trelles obtained SOP results, which is in quite good agreement with experimental observations but for arc discharge. 45 Raizer and Mokrov owed SOP formation to the instabilities caused by thermal expansion and/or electric field redistribution.…”
Section: Table 1 Types Of Plasma Devices With Formed Self-organized P...supporting
confidence: 84%
See 1 more Smart Citation
“…43 Bieniek et al also applied the same approach to simulate SOPs formed on the anode of DC glow discharge and found that the anode SOPs are related to the change in the sign of the near anode voltage. 44 Trelles obtained SOP results, which is in quite good agreement with experimental observations but for arc discharge. 45 Raizer and Mokrov owed SOP formation to the instabilities caused by thermal expansion and/or electric field redistribution.…”
Section: Table 1 Types Of Plasma Devices With Formed Self-organized P...supporting
confidence: 84%
“…[10][11][12] In parallel to experimental works, SOPs have been the subject of several theoretical studies considering various discharge configurations such as dielectric barrier discharge (DBD) discharge, 39,40 arc discharge, 41,42 and DC glow discharge. 43,44 Benilov modeled SOPs in DC glow discharge and/or arc discharge based on the first-principles equations containing all the relevant physical mechanisms and proposed that the cathode sheath instability is responsible for SOP formation on the cathode. 43 Bieniek et al also applied the same approach to simulate SOPs formed on the anode of DC glow discharge and found that the anode SOPs are related to the change in the sign of the near anode voltage.…”
Section: Table 1 Types Of Plasma Devices With Formed Self-organized mentioning
confidence: 99%
“…Significant achievements have also been made in numerical simulations. [22][23][24][25] For example, cylindrical DC glow discharges with liquid anodes were qualitatively modeled with results consistent with that of experiments. [26] This work assumes patterns are formed in a thin sheath layer just above the liquid water and treats local electron impacts contributing to ionization as an autocatalytic reaction.…”
supporting
confidence: 67%
“…It is known that numerical simulations are usually used to understand physical processes in the nearanode regions, since experiments of thin nearanode plasma layers are very difficult. Despite many simulations on the nearanode plasma layers over the past 30 years [25][26][27][28][29][30][31][32][33][34][35][36][37][38], the understanding of the nearanode region of arc plasma discharge is still insufficient. Tanaka et al [27] performed an analysis of the nearanode plasma layer with the quasineutral assumption in the freeburning argon arc.…”
Section: Introductionmentioning
confidence: 99%